A rapid and sensitive determination of hypoxic radiosensitizer agent nimorazole in rat plasma by LC‐MS/MS and its application to a pharmacokinetic study. (5th April 2015) - Das, Soumyajit; Dubey, Ramkumar; Roychowdhury, Subhradip; Ghosh, Manik; Sinha, Barij Nayan; Kumar Pradhan, Kishanta; Bal, Trishna; Muthukrishnan, Venkateswari; Seijas, Julio A.; Pujarid, Abhijit
Abstract A highly sensitive, accurate and robust LC‐MS/MS method was developed and validated for determination of nimorazole (NMZ) in rat plasma using metronidazole (MNZ) as internal standard (IS). The analyte and IS were extracted from plasma by precipitating protein with acetonitrile and were chromatographed using an Agilent Poroshell 120, EC‐C18 column. The mobile phase was composed of a mixture of acetonitrile and 0.1 % formic acid (85:15 v/v). The total run time was 1.5 min and injection volume was 5 μL. Multiple reaction monitoring mode using the transitions of m/z 227.1 → m/z 114.0 for MNZ and m/z 172.10 → m/z 128.1 for IS were monitored on a triple quadrupole mass spectrometer, operating in positive ion mode. The calibration curve was linear in the range of 0.25–200 ng/mL (r2 > 0.9996) and the lower limit of quantification was 0.25 ng/mL in the rat plasma samples. Recoveries of NMZ ranged between 88.05 and 95.25%. The precision (intra‐day and inter‐day) and accuracy of the quality control samples were 1.25–8.20% and −2.50–3.10, respectively. The analyte and IS were found to be stable during all sample storage and analysis procedures. The LC‐MS/MS method described here was validated and successfully applied to pharmacokinetic study in rats. Copyright © 2015 John Wiley & Sons, Ltd.